The Kiso Road : the life and times of Shimazaki Tōson - Naff, William E.; Rimer, J. Thomas; Walker, Janet A., 1942- (Honolulu : University of Hawaiʻi Press, 2011)
William E. Naff, the scholar of Japanese literature widely known for his translations of the writings of Shimazaki Toson (1872-1943), spent the last years of his life writing a full-length biography of Toson. The Kiso Road provides an account of this novelist who, along with Natsume Soseki and Mori Ogai, formed the triumvirate of writers regarded as giants in Meji Japan, all three of whom helped establish the parameters of modern Japanese literature. Professor Naff's biography places Toson in the context of his times and discusses every aspect of his career and personal life, as well as introducing a number of untranslated works.
Toson's long life, his many connection with other important Japanese artist and intellectuals, his sojourn in France during World War I, and his later visit to South America, permit a biography of depth and detail that serves as a kind of cultural history of Japan during an often turbulent period.
J. Thomas Rimer is professor emeritus of Japanese literature at the University of Pittsburgh. He has been the author, editor, of translator of many books, most recently two coedited volumes.
Janet A. Walker is professor of comparative literature at Rutgers University. She has published essays on both classical and Japanese literature, on the novel, and on South Asian literature. --Book Jacket.
Home and family: before 1872 -- Childhood and education: 1872-1892 -- A shaky start: 1892-1893 -- A poet's apprenticeship: 1893-1896 -- Escape to Sendai: 1896-1898 -- To Komoro: 1899-1900 -- From poetry to fiction: 1900-1904 -- A personal catastrophe, public triumph: 1905-1907 -- A bleak spring and a harsh summer: 1907- 1913 -- The French years: 1913-1916 -- A new life: 1916-1923 -- The open of the last act: 1923-1927 -- Before the dawn: 1927-1935 -- The final years: 1936-1943.
Includes bibliographical references (pages 633-648) and index.
Print version record.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
English.
Keywords: Shimazaki, Tōson, -- 1872-1943.; Shimazaki, Tōson, -- 1872-1943; Shimazaki, Tōson -- 1872-1943; Shimazaki, Tōson.; BIOGRAPHY & AUTOBIOGRAPHY -- Literary; BIOGRAPHY & AUTOBIOGRAPHY -- Cultural Heritage; Biography